The effectiveness and influencing factors of the “Y” line technique in reducing the leg length discrepancy after total hip arthroplasty - Jin, Wenshu; Sun, Huaqiang; Duan, Xudong; Gu, Yange; Zhao, Zhang; Yan, Xinfeng (Frontiers in Surgery, 2023)
Objective: To introduce a surgical technique (the ‘Y’ line technique) which is to control the leg length discrepancy (LLD) after total hip arthroplasty (THA), and observe its effectiveness and influencing factors. Methods: According to the inclusion and exclusion criteria, a total of 350 patients were selected; 134 patients who were used the ‘Y’ line technique to control lower limb length were included in Group A and 166 patients treated with free hand methods to control lower limb length were included in Group B. 50 patients who were taken standard anteroposterior X-ray of bilateral hips preoperatively and used the ‘Y’ line technique during the operation were included in Group C. Results: The postoperative LLD of Group A was 4.74 mm (3.93), Group B was 5.85 mm (4.60) and Group C was 2 mm (1.00) – the difference was statistically significant (p < 0.001). There were significant differences statistically in comparison between any two groups (P<0.01). The distribution of postoperative LLD in Group A was better than Group B, and Group C was better than Group A – the difference was statistically significant (p < 0.001). Severe unequal length rates of the lower extremities (LLD > 10 mm) were 5.97% (8/134) in Group A, 14.3% (24/166) in Group B and 0% (0/50) in Group C – the difference was statistically significant (p < 0.001). There were significant differences between Group A and Group B, Group B and Group C (P < 0.05), but there was no significant difference between Group A and Group C (P = 0.078). Conclusion: The ‘Y’ line technique, which does not increase the operation time and patient cost, can effectively reduce postoperative LLD. Insufficient internal rotation of the healthy lower extremity and the low projection position in the preoperative anteroposterior X-ray of bilateral hips were important factors affecting the accuracy of the ‘Y’ line technique.